2002
DOI: 10.1002/j.2050-0416.2002.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Industrial Strains ofSaccharomyces cerevisiaeReveals Numerous Altered Patterns of Maltose and Sucrose Utilisation

Abstract: A model fermentation system was used to define the abilities of 25 Saccharomyces cerevisiae strains, representing the brewing, baking, winemaking and distilling industries, to utilise maltose and sucrose in the presence of glucose and fructose. Three categories of sucrose and maltose utilisers were observed; repressible, constitutive and non-utilisers. In terms of fermentation kinetics, neither high rates of sucrose hydrolysis nor the early onset of maltose utilisation were correlated with reduced fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
5
35
0
3
Order By: Relevance
“…Brewer's wort contains the sugars sucrose, fructose, glucose, maltose, maltotriose, dextrin material, and a complex mixture of amino acids, peptides, proteins, vitamins, ions, nucleic acids and others constituents 32 . In the majority of industrial yeast fermentations a key requirement is the ability of the yeast strain to rapidly and efficiently utilise all sugars contained in the medium 21 . In order to elucidate the importance of amino acid spectrum and composition on yeast fermentation and beer flavor, the amino acid and peptide content and composition of wort and the removal of amino acids in a free and peptide form have been studied for many years 2,5,15,26,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brewer's wort contains the sugars sucrose, fructose, glucose, maltose, maltotriose, dextrin material, and a complex mixture of amino acids, peptides, proteins, vitamins, ions, nucleic acids and others constituents 32 . In the majority of industrial yeast fermentations a key requirement is the ability of the yeast strain to rapidly and efficiently utilise all sugars contained in the medium 21 . In order to elucidate the importance of amino acid spectrum and composition on yeast fermentation and beer flavor, the amino acid and peptide content and composition of wort and the removal of amino acids in a free and peptide form have been studied for many years 2,5,15,26,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Sugar catabolite repression ensures an ordered sequence of sugar utilisation, and during fermentation brewing yeast strains utilise sucrose, glucose, maltose and maltotriose in this approximate sequence, with some degree of overlap 32 . Altered patterns of sugar utilisation among strains have been reported 21 . Vital to industrial fermentation is the selection of yeast strains that rapidly and efficiently utilise all wort sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar catabolite repression 13,31 ensures an ordered sequence of sugar utilization, and during fermentation, brewing yeast strains utilize sucrose, glucose, maltose and maltotriose in this approximate sequence, with some degree of overlap 10 . However, altered patterns of sugar utilization among brewing, wine, baking and distilling strains have been reported 4,23 . Glucose and fructose are the main fermentable sugars in a wine must, and Saccharomyces cerevisiae is known to be glucophilic 12 , and despite being concomitantly used with glucose, fructose is the main sugar present in the later stages of alcoholic fermentation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the preference for glucose over fructose is strain dependent, and the discrepancy between glucose and fructose consumption is not a fixed parameter, but is dependent on the yeast's genetic background and on external conditions 4 . For these reasons, one criterion considered in selecting industrial strains for the brewing, baking, wine and distilling industry is their capability to rapidly and completely utilize the fermentable carbohydrates present 23,30 . However, in industrial brewing worts and wine musts, carbohydrates are not the only important group of compounds in the medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation